Analisis Sakti Dalam Pelaporan Bendahara Pengeluaran Di BBPPKS Regional III Yogyakarta - Becdivanto Trianjas Hutomo Aji; Reni Yendrawati (Jurnal Akuntan Publik, 2023)
Society demands public sector organizations to be able to manage public services and provide them in an accountable, participative and transparent manner. SAKTI or Institutional Level Financial Application System is an application that is used as a means of work units in supporting the implementation of SPAN to carry out financial management which includes the planning stages to budget accountability. The purpose of this research is to observe how SAKTI works and to analyze the system, with the implications of whether it provides convenience in the performance of work units of government agencies. This type of research is descriptive qualitative and the method for collecting data used is direct observation with field research and library research, and the information will be filtered through descriptive analysis methods. The research results that have been achieved are that SAKTI is a new effectiveness. The advantage of using SAKTI is that it has an open platform, so it can be accessed anywhere and anytime, and provides efficient integration. Weaknesses in the use of SAKTI is the user's understanding in technical operations, so it requires sufficient training and another deficiency is the internal control of the organization. The conclusion of this research is that in the era of technology that pressures society for optimal and in-depth digital understanding. Suggestions by the author are to integrate a digital concept in the work system of the work unit, more understanding is needed so that it does not become an obstacle.